SMEs and Women-owned SMEs in Mongolia : Market Research Study - International Finance Corporation (Washington, DC, 2015)
Chapter one summarizes the scope of the study and outlines its key objectives. It explains the rationale for collecting data on SMEs in Mongolia in general and women-owned SMEs in particular. It also provides recommendations for integrating the insights form the study into the on-the-ground practice of SME banking, as well as potential interventions on the regulatory and policy level. Chapter two begins with the analysis of the general macroeconomic context and provides an overview of the SME sector in Mongolia. The chapter analyzes the latest trends in development of the business environment and the legal framework relevant for SMEs and women-owned SMEs. Chapter three examines the aspect of supply in financial and non-financial products and services currently offered to SMEs by commercial banks and non-bank financial institutions. It also reviews the support provided to SMEs by international financial institutions. Chapter four provides detailed overview of the findings of the demand study, explores the features of SMEs, their relationships with banks and NBFIs as well as aspects of current use of bank loans. The chapter further analyzes the usage and demand for other banking products and services by SMEs. Chapter five summarizes the key constraints faced by the SMEs and female-owned SMEs revealed in the interviews with stakeholders and the face to-face interviews with business owners. Finally, chapter six uses the findings to draw conclusions and recommendations on possible measures to address the challenges of SMEs and women-owned SMEs specifically at different stakeholder levels: governmental and regulatory authorities, international finance institutions, financial institutions and SME development organizations.